IMPLEMENTATION OF RELIGIOUS EXTRACURRICULAR ACTIVITIES IN DEVELOPING STUDENTS’ INTERESTS AND TALENTS AT MADRASAH TSANAWIYAH AL HIDAYAH RAWABENING BK3 BUAY MADANG EAST DISTRICT, EAST OKU DISTRICT - ILHAM (UNISAN JURNAL, 2024)
This research aims to explore the implementation of extracurricular activities in developing students’ interests and talents. Extracurricular activities provide opportunities for students to explore their interests and talents in various fields such as arts, sports, science, and others. This research uses qualitative methods by analyzing data from interviews with students, supervising teachers, and managers of extracurricular activities in two secondary schools in a metropolitan city. The research results show that extracurricular activities make a significant contribution to developing students’ interests and talents. Education participants who are involved in extracurricular activities feel more motivated and enthusiastic about participating in activities outside the classroom. They also develop skills such as discipline, hard work, and team collaboration through active participation in clubs, organizations, or extracurricular teams. In addition, extracurricular activities also provide opportunities for students to explore their special interests and prepare themselves for future careers. Learners who have an interest in a particular field such as science, sports, or the arts can gain useful experience and build a network that can help them achieve their career goals. In conclusion, implementing extracurricular activities effectively can increase the development of students’ interests, talents and skills. Therefore, it is recommended that educational institutions provide greater support for extracurricular activities as an integral part of holistic and comprehensive education.